The Influence Of Price And Airline Brand Image On Airplane Ticket Purchase Decisions At PT Arimbi Jaya Tour And Travel - Agus Widodo; Liling Listyawati; Moch Arfani; Damajanti Sri Lestari (Cita konsultindo, 2025)
The rapid advancement of digital technology has significantly transformed the marketing landscape, especially in the aviation industry. This study investigates the influence of price and brand image on the decision to purchase airline tickets at PT Arimbi Jaya Tours and Travel. Utilizing quantitative research methods, data were collected through electronic questionnaires distributed via Google Forms. The findings indicate that price and Brand Image play a crucial role in shaping consumer decisions, as customers are increasingly attracted to competitive prices and strong brand identities. This study highlights the importance of effective marketing strategies in enhancing customer satisfaction and loyalty in a highly competitive environment, especially post-pandemic when travel demand has rebounded.